2022
DOI: 10.1097/md.0000000000029197
|View full text |Cite
|
Sign up to set email alerts
|

CT findings of basaloid squamous cell carcinoma of the lung in 12 patients

Abstract: Basaloid squamous cell carcinoma (SCC) is very rare subtype of SCC of the lung and it is important to distinguish basaloid to other subtypes of SCCs, since the prognosis of basaloid subtype is considered poorer than that of other non-basaloid subtypes of SCCs. Aim of this study was to assess computed tomography (CT) findings of basaloid SCC of the lung in 12 patients.From January 2016 to April 2021, 12 patients with surgically proven basaloid SCC of the lung were identified. CT findings were analyzed, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In our study, cavitation was seen in 15.5% of non-basaloid SCC, which corresponded to known prevalence of cavitation in lung cancers. However, none of the basaloid SCCs showed cavitation, in concordance with our previous study [13]. Furthermore, in our study, basaloid SCCs showed less frequent internal profuse necrosis on CT than non-basaloid SCCs.…”
Section: Clinical T and N Stagingsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, cavitation was seen in 15.5% of non-basaloid SCC, which corresponded to known prevalence of cavitation in lung cancers. However, none of the basaloid SCCs showed cavitation, in concordance with our previous study [13]. Furthermore, in our study, basaloid SCCs showed less frequent internal profuse necrosis on CT than non-basaloid SCCs.…”
Section: Clinical T and N Stagingsupporting
confidence: 92%
“…In concordance with our study, majority of basaloid SCCs in previous literatures presented as nodules or masses without cavitation [3,13,[22][23][24]. Yet, some exceptions exist.…”
Section: Clinical T and N Stagingsupporting
confidence: 91%
See 3 more Smart Citations